(untitled) - Leifer, Gloria (St. Louis ( Missouri ), 2015)
Part of the popular LPN Threads series, this market-leading text provides coverage of basic maternity and pediatric nursing in one convenient text. Material is presented with a logical and effective simple-to-complex and health-to-illness organization. With an emphasis on prevention, early recognition, and the family, this edition also includes enhanced coverage of antepartum care and a new full-color design.
Keywords: Maternity nursing,Pediatric nursing,Maternal-Child Nursing,Pediatric Nursing,Điều dưỡng thai sản,Điều dưỡng nhi,Điều dưỡng bà mẹ-trẻ em,Điều dưỡng nhi; Methods,Methods